LEGAL CERTAINTY FOR THE REMOVAL OF CHILD CUSTODY DUE TO NEGLIGENCE OF BIOLOGICAL PARENTS (Lex Jurnalica, 2018)
AbstractUnitary Republic of Indonesia in ensuring the welfare of every citizen one of which is to provide protection of children's rights, which is one of human rights. The Indonesian government in its efforts to ensure in realizing the protection and welfare of children is through the promulgation of Law No. 35 of 2014 on Protection of Children. The protection of children as defined in Article 1 paragraph 2 of the Act are all activities to ensure also protect children and their rights in order to live, grow, develop and participate optimally in accordance with human dignity, as well as protection from violence and discrimination. This study uses normative juridical approach, namely by reviewing or analyzing secondary data in the form of secondary legal materials to understand the law as a set of rules or norms of positive law within the system. This is what the writer would do the assessment, considering the fact that there are many cases legal protection of children certainly concern us all, especially neglect of the child by his biological parents.Â Keywords: Protection of children, neglect (negligence) of parents, the revocation of custody of childrenAbstrakNegara Kesatuan Republik Indonesia dalam menjamin kesejahteraan pada setiap warga negaranya salah satunya adalah dengan memberikan perlindungan terhadap hak anak yang merupakan salah satu dari hak asasi manusia. Pemerintah Indonesia dalam usahanya untuk menjamin dalam mewujudkan perlindungan dan kesejahteraan anak adalah melalui pembentukan Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak. Perlindungan anak sebagaimana dimaksud dalam Pasal 1 angka 2 Undang-Undang tersebut adalah segala kegiatan untuk menjamin juga melindungi anak dan hak-haknya agar dapat hidup, tumbuh, berkembang, dan berpartisipasi secara optimal sesuai dengan harkat dan martabat kemanusiaan, serta mendapat perlindungan dari kekerasan dan diskriminasi. Penelitian ini menggunakan pendekatan Yuridis Normatif, yaitu dengan mengkaji atau menganalisa data sekunder yang berupa bahan-bahan hukum sekunder dengan memahami hukum sebagai perangkat peraturan atau norma-norma positif didalam sistem perundang-undangan. Hal inilah yang oleh penulis hendak melakukan pengkajian, mengingat dari fakta hukum yang ada banyak kasus perlindungan anak tentu saja memprihatinkan kita semua terutama penelantaran anak oleh orangtua kandungnya.Kata kunci: Perlindungan anak, pengabaian (kelalaian) orang tua, pencabutan hak asuh anak